Marketing ethics and consumer society : practising inclusive, responsible and sustainable marketing - Daskalopoulou, Athanasia; Yannopoulou, Natalia (Routledge, 2025)
"This unique new text explores marketing ethics, the impact of marketing on consumers' lives, and the wider social, cultural, and political context of marketing activities. Taking a critical approach to marketing practice, the book discusses the growing sense of responsibility within the marketing discipline and addresses issues at the interface between marketing and society. Importantly for Marketing students, it works to develop an understanding of the impacts that marketing can have on consumers' lives and the potential that future marketers have to shape contemporary society. Chapters cover Marketing and Advertising Ethics, Critical Consumption, Gender and Race, Brand Activism, Sustainability and Corporate Social Responsibility, and Understanding and Protecting the Consumer. Case studies drawn from international contexts featuring real-life and recognisable organisations are included in every chapter to bring the theory to life, enabling students to explore the ethical dilemmas and criticisms faced by organisations and consumers in contemporary society. Chapter outlines, learning outcomes, summaries, and self-assessment questions cement learning, whilst discussion questions aim to provoke interesting conversation. A much-needed and relevant textbook that brings together all the key contemporary topics in marketing ethics, this should be core reading for advanced undergraduate and postgraduate students studying modules on Marketing Ethics, Ethical Marketing and Sustainability, and Marketing and Society. Online support materials include lecture slides and a test bank"-- Provided by publisher.
Keywords: Marketing -- Moral and ethical aspects.; Marketing -- Social aspects.; Social responsibility of business.; elektronické knihy; electronic books